2021
DOI: 10.1021/acs.est.1c01974
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Persistent Free Radicals (PFRs) Formed as Crucial Metastable Intermediates during Peroxymonosulfate (PMS) Activation by N-Doped Carbonaceous Materials

Abstract: A nonradical mechanism involved in peroxymonosulfate (PMS) activation in carbonaceous materials (CMs) is still controversial. In this study, we prepared N-doped CMs, including hollow carbon spheres (NHCSs) and carbon nanotubes (N-CNTs), to probe the crucial intermediates during PMS activation. The results suggested that the higher efficiency and lower activation energy (13.72 kJ mol–1) toward phenol (PN) degradation in an NHCS/PMS system than PMS alone (∼24.07 kJ mol–1) depended on a typical nonradical reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(16 citation statements)
references
References 74 publications
0
16
0
Order By: Relevance
“…The contents of VOCs in biochar decreased with increasing HTTs (Buss et al 2015). Numerous studies have reported the stable and large molecular PFRs in biochar during the biomass carbonization process (Liao et al 2014;Lieke et al 2018;Yang et al 2016;Zhen et al 2021). It was found that the electron paramagnetic resonance (EPR) signals in lignin-derived biochar were higher than those in cellulose-derived biochar.…”
Section: Discussionmentioning
confidence: 99%
“…The contents of VOCs in biochar decreased with increasing HTTs (Buss et al 2015). Numerous studies have reported the stable and large molecular PFRs in biochar during the biomass carbonization process (Liao et al 2014;Lieke et al 2018;Yang et al 2016;Zhen et al 2021). It was found that the electron paramagnetic resonance (EPR) signals in lignin-derived biochar were higher than those in cellulose-derived biochar.…”
Section: Discussionmentioning
confidence: 99%
“…The extensive use of antibiotics, pharmaceuticals, organic dyes, and industrial chemicals has released increasing amounts of organic contaminants in the environment, posing a great threat to the ecological environment and human beings . Reactive oxygen species-based advanced oxidation processes (AOPs) have exhibited significant potential in the broadband abatement of refractory pollutants in aqueous systems. , Among these, persulfate-mediated Fenton-like processes including peroxymonosulfate (PMS) and peroxydisulfate are attracting enormous interest owing to the generated highly oxidative oxygen species such as sulfate radicals, hydroxyl radicals, and superoxide radicals . By cleaving O–O bonds in PMS molecules via electron and energy transfer processes, the most commonly reactive species of sulfate radicals [E 0 (SO 4 •–/SO 4 2– ) = 2.60 ∼ 3.10 V NHE ] and hydroxyl radicals [E 0 (•OH/OH – ) = 1.90 ∼ 2.70 V NHE ] can be formed and further attack organic compounds .…”
Section: Introductionmentioning
confidence: 99%
“…After reacting with Cr(VI) at pH 3.0-9.0, the binding energy peak of pyrrolic-N shifted from 399.8 to 400.0 eV (Fig. 5d-g), meaning only pyrrolic-N acted as electron donor for Cr(VI) reduction 42 . The proportion of pyrrolic-N after reaction at pH 3.0-9.0 decreased to 40.52-43.8% (Fig.…”
Section: Resultsmentioning
confidence: 98%